Evidence for a novel mechanism of influenza A virus host adaptation modulated by PB2‐627. (5th July 2019) - Liu, Xiaokun; Yang, Cha; Sun, Xiaomei; Lin, Xian; Zhao, Lianzhong; Chen, Huanchun; Jin, Meilin
Abstract : Influenza virus cross‐species transmission is restricted by the host, but viruses overcome this restriction by accumulating mutations which allow them to adapt to a new host. Among the many factors which facilitate virus host adaptation, polymerase basic protein 2 ( PB2 ) 627 plays an important role, although the underlying molecular mechanism has not been fully understood. In a previous study, we found that histone H1.2 (encoded by HIST1H1C ) regulates human or avian influenza virus replication in different ways, indicating that it might be involved in virus host adaptation. Herein, we found that HIST1H1C expression, phosphorylation and methylation levels are decreased when infected with H1N1 influenza virus and increased when infected with H5N1 influenza virus. Overexpressing the eight gene segments of the influenza virus, we found that only PB2 significantly affects HIST1H1C expression and modifications. Since the 627 site is different between the H5N1 and H1N1 influenza viruses we constructed PB2‐627E (avian variant) and PB2‐627K (human variant) mutant viruses, and observed that the effects of the wild‐type and the mutant viruses on HIST1H1C expression and modifications are the opposite of one another. Further analysis showed that influenza virus PB2‐627 regulates HIST1H1C expression via Sp1, and specifically that PB2‐627K down‐regulates Sp1 and HIST1H1C while PB2‐627E up‐regulates Sp1 and HIST1H1C . In addition, HIST1H1C can feedback regulate DNA‐dependent protein kinase and euchromatic histone‐lysine N ‐methyltransferase 1/2, leading to altered HIST1H1C phosphorylation and methylation levels, and affecting influenza virus replication accordingly. In summary, this study illustrates the mechanism of PB2‐627E/K ‐mediated regulation of influenza virus host adaptation. Abstract : When avian influenza viruses (AIV) infect mammalian cells, PB2‐627E increases Sp1 expression, which up‐regulates HIST1H1C . HIST1H1C promotes DNA‐PK and EHMT1/2 expression by feedback regulation, increasing phosphorylation and methylation of HIST1H1C . While phosphorylated HIST1H1C enhances IFN‐β expression, methylated HIST1H1C represses IFN‐β and in this way promotes AIV replication. Conversely, human influenza virus (hIV) infection down‐regulates Sp1, leading to decreased HIST1H1C expression, phosphorylation and methylation. Lower methylation releases IFN‐β inhibition by HIST1H1C, thereby blocking hIV replication.